IMPLEMENTING SCIENTIFIC APPROACH IN THE 2013 CURRICULUM AT GRADE I SDN 006 SUNGAI ARA - Nurmarsitin Nurmarsitin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The purpose of this study was to improve learning by using scientific approach in the 2013 curriculum. This study was conducted thorugh the classroom action research method. The results of this study obtained from the assessment of self-confidence indicated that 17 people (53.13%) has cultivated their self-confidence, 15 people (46.88%) started to develop their self-confident, 0 people (0%) started to show their self-confidence, and 0 people (0%) did not yet show their self-confident. Then, 14 students demonstrated their discipline attitude (43.75%), 12 people (37.5%) were starting to develop their discipline attitude, 6 people (18.75%) were starting to demonstrate their discipline attitude, and 0 people (0%) did not yet show their discipline attitude. Moreover, it was found that 12 students had cultivated a cooperative attitude (37.5%), 14 people (14.75%) were starting to develop a cooperative attitude, 6 people (18.75%) were starting to show a cooperative attitude, and 0 people (0%) did not yet show a cooperative attitude. In addition, based on the knowledge assessment in Cycle I, 10 students got a Very Good score (31.25%), 12 students got a Good score (37.5%), 8 students got a Fairly Good score (25%), and 2 students needed a score (6.25%). Whereas in Cycle II, it was seen that 22 students got a Very Good score(68.75%), 8 students got a Good score(25%),1 student got a Fairly Good score (3.13%), and 1 student needed a guidance(3.13%).